What Is Applied Behavior Analysis? I know I understand nothing: Invitation to Discussion - Wloch, Danuta (Forum pedagogiczne, 2023)
The aim of this study in the qualitative approach is to thoroughly analyse the phenomenon of ABA and to present the perception of ABA by people working with children with ASC[1] and by me to obtain a more accurate and reliable picture of the entirety of the examined problem. I will try to explain the various meanings given to ABA and the resulting misunderstandings. This will also be an attempt to consider what professionals working with autistic children criticise or support when talking about ABA.Another goal is to organise knowledge on the subject by showing the historical background.